2008
DOI: 10.13057/biodiv/d100310
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Lobak Leaves (Raphanus sativus L. var. hortensis Back) as Anticancer and Antimicrobial Candidates

Abstract: One of vegetables can preventive cancer and have been used traditionally to cure infection, such as lobak (Raphanus sativus L.). Ineffectiveness antibiotics against microbial infections were still problem until now. Types of antibiotics and anticancer agents from natural resources should be explored and developed. This study was aimed to know toxicity effect and antimicrobial activity of active fractions from lobak leaves. Toxicity study was conducted using Brine Shrimp Lethality Test (BST). Samples were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…This indicated that the toxic compounds in the EC exerted a synergistic effect [35]. Based on the anticancer preliminary test (toxicity test), the EC was the most toxic extract, indicating that the toxic compounds are semipolar because they dissolve into chloroform (Table-2) [36]. As shown in Figure-1, the sample concentration was positively correlated with the inhibition of HeLa cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the toxic compounds in the EC exerted a synergistic effect [35]. Based on the anticancer preliminary test (toxicity test), the EC was the most toxic extract, indicating that the toxic compounds are semipolar because they dissolve into chloroform (Table-2) [36]. As shown in Figure-1, the sample concentration was positively correlated with the inhibition of HeLa cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl acetate fraction from methanol extract is most active that had larger clear zone in S. aureus culture (10,64 mm). Bioactive compounds at active fraction were identified to contain polar compounds [24] .…”
Section: Anti Inflammatory Activitymentioning
confidence: 99%
“…Melalui metode BSLT pelaksanaan skrining awal dapat dilakukan dengan biaya yang relatif mudah, sederhana, dan relatif cepat terhadap standarisasi bioaktifitas pada produksi tumbuhan heterogen (12). Suatu ekstrak dikatakan bersifat toksik jika memiliki nilai LC50 (konsentrasi yang mampu membunuh 50% larva udang) kurang dari 1000 ppm setelah waktu kontak 24 jam (13).…”
Section: Perhitungan Nilai Lc50unclassified